EXCAVATIONS IN FROZEN GROUND. IGLOO FOXHOLES - Benert, Robert (1960)
Tests were conducted near Houghton, Mich., in December 1954 to determine the feasibility of producing man-sized cavities beneath the frozen ground layer. Charges from 0.1-10 lb of low-velocity explosives (Coalite 7S and Gelodyn 1) were fired at depths from 10.5-48 in. in ground frozen to a depth of 6-24 in. The development of these igloo-shaped foxholes by explosive is not recommended since it is not possible to predict accurately the amount of explosive required and the igloo shape is not suitable for combat areas. However, 1 to 2 lb of Coalite 7S is sufficient to produce a 24-in. diam crater in ground frozen to a depth of 1 to 2 ft. The crater can be enlarged easily by excavating the underlying thawed ground.